Leadership for competitive advantage - Georgiades, Nick (John Wiley, 1998)
Leadership for Competitive Advantage answers the real and complex needs of leaders attempting to balance the seemingly conflicting demands of a turbulent external environment and the needs of shareholders, customers and employees. The book contains an interesting model which is a guide to sorting and assigning priorities for action. It enumerates the key steps in the process of making significant change and offers hints and practical advice to help the reader on his or her own individual journey.